Drug Abuse Among Adolescents - Susanti, Nofi; Cahyani, Eka; Hidayah, Nurul; Aprillia, Rezky (CV. Rayyan Dwi Bharata, 2024)
This study examines the decline in the number of drug abuse cases among teenagers based on data from e-MP Robinopsnal Bareskrim Polri. The data covers the period from January 1 to January 21 over three consecutive years. The findings show a significant decrease in the number of reported cases, from 19,375 cases in 2021 to 6,450 cases in 2023. This decline indicates effective efforts in the prevention and handling of drug abuse among teenagers.